PENDEKATAN ANTROPOLOGI LAPANGAN EDWARD EVANS-PRITCHARD DALAM KAJIAN ISLAM - Kholid mawardi (Komunika, 2015)
Islam, as a science, shoud be viewed equally as other disciplines. One of the poin is that other disciplines should be applied as an approach to Islamic studies, since there has been a tense on whether Islam should be studied normatively or historically. Those two approaches have different assumptions. Considering the development of global knowledge, historical approach in Islamic studies should be firstly apllied. This means that other disciplines such as sociology, psychology and antropology should be applied in Islamic studies. This article introduces Edward Evans-Pritchard’s Islamic studies with antropological approach which stated that it is necessary to emphasize on the study of religions and primitive beliefs in its real life and beyond literary and teological texts. One valid theory will explain a religion as it grows in the society, not as perceived by its preachers, so that the power and growth of a religion can be reached.